The Investment Bank’s Reputation And The Price Of Underwriting Services: Evidence From China - Li, Yubo (European Scientific Journal, ESJ, 2016)
In this paper, I examine the influence of the investment bank’s reputation on the price of underwriting services of Chinese firm. Based on a sample of offers from 2004-2015, the results show that prestigious investment banks charge higher fees. Furthermore, in comparison to big firms, prestigious investment banks charge more underwriting fees for small firms. In comparison to state-owned firms, high-reputation investment banks charge higher underwriting fees for non-state-owned firms. The results indicate that the investment bank’s reputation capital is different for different firms. For firms with more information problems, the reputation of investment banks is more valuable.